Pengalihan Kewenangan Pemberian Izin Usaha Pertambangan Mineral-Batubara Oleh Pemerintah Daerah - Iqbal Shalihin (Nagari Law Review, 2018)
With the enactment of Law Number 23 of 2014 on Regional Government, there is a change of authority between the central government, provincial and district governments. Article 4 paragraph (1) of the Law says that "the administration of the forestry affair, marine and mineral resources energy is divided between government and government province". When viewed from the matrix of division of authority between the central government, provincial government and thedistrict (kabupaten)/ city (kota) government it will be very clear that the district government does not have the authority, as under the previous Law on Regional Government. The problem will cause disputes between the provincial and district governments in issuing permit in mining because mining has been the source of income for the regions. In the Law Number r23 of 2014 on the Regional Government of the district / City Government does not have the authority to issue IUP (Mining Business License). Article 37 of Law Numberr 4 of 2009 concerning Mineral and Coal Mining states that the Regency / City Government has the authority to issue Mining Permit or IUP. This regulation then becomes an obstacle in its application, especially at the regional level as does the province of Western Sumatra, because there is no technical rule that can then become the base of rights for the provincial government to take over the authority of the district government as mandated by Law Number 23 of 2014 on Regional Government. Under such conditions the Ministry of Home Affairs issued a Circular Letter of the Minister of Home Affairs No.120 / 253 / SJ on the Implementation of Government Affairs After the enactment of Undang-Undang Nomor 23 Tahun 2014